FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL SUATU PERUSAHAAN - Elfreda Aplonia Lau (Exchall: Economic Challenge, 2022)
This study aims to examine the theory and several studies on the factors that affect the capital structure of a company. The theories used in this research are Balancing Theories, Pecking Order Theory, Financial Distress and Agency Costs, Modigliani and Miller (MM) Approach, Trade off Theory and Signaling theory. The results of the research examined in this study are research conducted by Ariyanto (2020), Lisiana and Widyarti (2020), Umdiana and Nurjanah (2020), Hasanah Nurohim and Komariah and Nurulrahmatiah (2020), Mahanani and Asandimitra(2017). The findings of this study indicate that the capital structure is influenced by many factors including interest rates, earning stability, asset composition, asset risk levels, the amount of capital required, the state of the capital market, the nature of the company, and the size of a company. The effect of interest rates, earnings stability, asset composition, asset risk levels, the amount of capital required, capital market conditions, the nature of the company and the size of the company on the capital structure of a company varies widely among researchers. This variable influence is highly dependent on the measuring instrument for the independent variable and the dependent variable (capital structure), the financial condition of a company,economic situation and management policies.